2001
DOI: 10.1161/hh2001.098983
|View full text |Cite
|
Sign up to set email alerts
|

On the Role of Ca 2+ - and Voltage-Dependent Inactivation in Ca v 1.2 Sensitivity for the Phenylalkylamine (-)Gallopamil

Abstract: Abstract-L-type calcium channels (Ca v 1.m) inactivate in response to elevation of intracellular Ca 2ϩ (Ca 2ϩ -dependent inactivation) and additionally by conformational changes induced by membrane depolarization (fast and slow voltage-dependent inactivation). Molecular determinants of inactivation play an essential role in channel inhibition by phenylalkylamines (PAAs). The relative impacts, however, of Ca 2ϩ -dependent and voltage-dependent inactivation in Ca v 1.2 sensitivity for PAAs remain unknown. In ord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 42 publications
2
10
0
Order By: Relevance
“…7B). Our finding that verapamil accelerates the inactivation of Ca v 1.2 channels and increases the fraction of channels inactivating is consistent with previous studies (Johnson et al, 1996;Sokolov et al, 2001). However, our results with EIIIQ are in contrast to observations with mutations in IVS6 which accelerated both verapamil block and recovery from verapamil block at ϩ10 mV (Johnson et al, 1996).…”
Section: Potentiation Of Closed-channel Block and Frequencydependent supporting
confidence: 93%
“…7B). Our finding that verapamil accelerates the inactivation of Ca v 1.2 channels and increases the fraction of channels inactivating is consistent with previous studies (Johnson et al, 1996;Sokolov et al, 2001). However, our results with EIIIQ are in contrast to observations with mutations in IVS6 which accelerated both verapamil block and recovery from verapamil block at ϩ10 mV (Johnson et al, 1996).…”
Section: Potentiation Of Closed-channel Block and Frequencydependent supporting
confidence: 93%
“…2ϩ potentiation of the LTCC block has been observed for different PAAs (8,55,56). In our models, a Ca 2ϩ ion bound to the side chains of E 3p50 and E 4p50 is coordinated by the nitrile nitrogen of PAAs.…”
Section: Effect Of Ca 2ϩ On Three Classes Of Ltcc Ligands-camentioning
confidence: 65%
“…C, change in peak current amplitude measured at ϩ10 mV from a holding potential of Ϫ60 mV when the extracellular solution is switched from 10 mM Ba 2ϩ to 10 mM Ca the modulation of (Ϫ)-gallopamil (a PAA) block of Ca v 1.2 by different ␤ subunits (Sokolov et al, 2001) concluded that channels with an accelerated voltage-dependent inactivation rate were also more sensitive to gallopamil block. Furthermore, Sokolov et al (2001) proposed that PAA block of Ca v 1.2 depends upon the fast voltage-dependent inactivation observed in Ba 2ϩ and not the further acceleration of inactivation observed in Ca 2ϩ . Thus, our data fit well with the model of Sokolov et al (2001), since the main effect of the I1627A mutation is to shift Ͼ80% of channels into the fast inactivating mode in Ba 2ϩ (i.e., the fast voltage-dependent inactivation of Sokolov et al, 2001; Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Sokolov et al (2001) proposed that PAA block of Ca v 1.2 depends upon the fast voltage-dependent inactivation observed in Ba 2ϩ and not the further acceleration of inactivation observed in Ca 2ϩ . Thus, our data fit well with the model of Sokolov et al (2001), since the main effect of the I1627A mutation is to shift Ͼ80% of channels into the fast inactivating mode in Ba 2ϩ (i.e., the fast voltage-dependent inactivation of Sokolov et al, 2001; Fig. 8C).…”
Section: Discussionmentioning
confidence: 99%